The Participate in the Add Value to Products for the Development of self-reliant Community Enterprises: A Case study of Khonsawan District, Chaiyaphum Province: The Participate in the Add Value to Products for the Development of self-reliant Community Enterprises: A Case study of Khonsawan District, Chaiyaphum Province - Romepan, Thammarat; Srichan, Thanikarn; Intaraprajob, Inthuraporn (RATANABUTH JOURNAL, 2025)
This research aims to study: 1. The level of knowledge and understanding affecting the participation in adding value to the product for the development of self-reliant community enterprises. 2. The level of participation in adding value to the product for the development of self-reliant community enterprises. 3. Problems and solutions to the participation in adding value to the product for the development of self-reliant community enterprises. The population and sample were analyzed by using the Krejcie & Morgan table. The number of samples was 248. The research results were as follows: 1. The knowledge and understanding of adding value to the product for the development of self-reliant community enterprises found that the people in the weaving community enterprise group had knowledge and understanding of adding value to the product for the development of self-reliant community enterprises, with 97.17 percent correct answers and 13.30 percent incorrect answers for the question about free gifts. 2. The level of participation of the people in adding value to the development of self-reliant community enterprises found that the people in the weaving community enterprise group had opinions on adding value to the development of self-reliant community enterprises overall at a moderate level (= 2.67). When considering each item, it was found that the issue in which the sample group participated the most You benefit from product development to add value to hand-woven fabric products to create a career to increase family income (= 3.55). Next is that you benefit from having knowledge in product development to add value to hand-woven fabric products more (= 3.46). And the least participation is that you participate in monitoring and inspecting the leaders and committees in the work of your community enterprise group (= 2.06). 3. Opinions on problems and solutions for participation in adding value to products for community enterprise development. Local administrative organizations should strengthen community enterprise groups and provide opportunities for public participation in setting strategic directions for product development to increase value-added.